2000
DOI: 10.1034/j.1399-3054.2000.100209.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical experimental evaluation of methods for determination of NH4+ in plant tissue, xylem sap and apoplastic fluid

Abstract: Ammonium (NH4+) is a central intermediate in the N metabolism of plants, but the quantitative importance of NH4+ in transporting N from root to shoot and the capability of plants to store NH4+ in leaves are still matters of substantial controversy. This paper shows that some of these controversies have to be related to the use of inadequate analytical procedures used for extraction and quantification of NH4+ in plants. The most frequently used methods for determination of NH4+, viz. colorimetric methods based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 48 publications
2
92
0
1
Order By: Relevance
“…Details of the analytical procedures can be obtained from Husted et al (2000a), Mattsson et al (2009) and Wang et al (2011). In brief, chlorophyll was extracted from frozen plant materials by the use of methanol.…”
Section: Analysis Of Plant Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the analytical procedures can be obtained from Husted et al (2000a), Mattsson et al (2009) and Wang et al (2011). In brief, chlorophyll was extracted from frozen plant materials by the use of methanol.…”
Section: Analysis Of Plant Tissuesmentioning
confidence: 99%
“…The driver for NH 3 exchange between plants and the atmosphere is the stomatal compensation point for NH 3 , reflecting external N availability and internal plant processes involved in N assimilation and turnover (Mattsson and Schjoerring, 1996; al. Husted et al, 2000b;Massad et al, 2008). The stomatal compensation point for NH 3 is a function of leaf temperature and the concentrations of NH + 4 and H + in the leaf apoplastic solution.…”
Section: Grass Seasonal Nh 3 Exchange Potentialmentioning
confidence: 99%
“…Free ammonium was determined fluorometrically according to Husted et al (2000) following derivatization at 638C with 3 mM O-phthalaldehyde and 10 mM 2-mercaptoethanol (in 0.2 M Tris-HCl, pH 6.8) and quantification in an HPLC system (HP 1100; Hewlett-Packard). Ammoniun concentration was also determined as the amount of NADH oxidized via the aminating reaction of GDH at 340 nm at room temperature in a total reaction volume of 0.5 mL consisting of 100 mM Tris, pH 8.0, 15 mM 2OG, 1 mM CaCl 2 , 1 mM NADH, and 2 units of GDH (1 mg protein equals 46 units; Sigma-Aldrich).…”
Section: Ammonia Extraction and Determinationmentioning
confidence: 99%
“…2B). Husted and coworkers [16] reported that amino acids interfere with the Berthelot reaction when present in high concentration as compared with ammonium. We found that activated charcoal efficiently absorbed most of the amino acids from an aqueous solution (data not shown) This partial purification by charcoal makes the Berthelot reaction suitable for plant extracts.…”
mentioning
confidence: 99%
“…The protocol presented in Ref. [16] requires elaborate instrumentation, whereas the novel extraction and purification protocol presented here allows reliable and efficient quantification of ammonium with a spectrophotometer. However, if this new protocol is to be adapted for different tissues or plant species, we recommend optimizing the relative amounts of extract to activated charcoal to minimize interference as described above.…”
mentioning
confidence: 99%